Process manuals for the diagnosis and maintenance of electrical micromobility - Ramírez Álvarez , Juan Diego (2025)
Nowadays, companies worldwide operate through processes, which generates the need to control each one of them to guarantee efficiency. The objective was to design a process manual for the diagnosis and maintenance of electrical micromobility based on time standards. The study has a quantitative approach, like a feasible project, a documentary design. The sample consists of scientific, technical and manual studies. To collect information, the document analysis technique was applied and the instrument consisted of an analysis matrix. The results show that the proposed manual is designed as an organized, detailed and systematic guide for the work of diagnosis and maintenance of electrical micromobility. It is concluded that, to achieve effective management, it is suggested to follow the steps established in the manual in this way, using the available means for the different tasks that are carried out in the diagnosis and maintenance of electrical micromobility